Pain in full term newborns submitted to music and swaddling during venipunctures - Tamires Rebeca Forte Viana; Gleicia Martins de Melo; Maria Vera Lucia Moreira Leitão Cardoso; Paulo César de Almeida; Lusiana Moreira de Oliveira; Daisyanne Augusto de Sales Santos (Universidade Federal do Ceará, 2020)
Objective: to compare pain scores in term newborns submitted to music and swaddling interventions during venipuncture. Methods: pilot study of a clinical trial, carried out with 11 newborns in rooming-in care who received venipunctures. The newborns were randomly allocated into two groups: Experimental (20 minutes of music + swaddling) and Control (swaddling). Newborns were filmed and pain was assessed by the Neonatal Facial Coding System at baseline, procedure, and initial recovery phases. Results: the Experimental Group at baseline, procedure (antisepsis, puncture, and milking), and recovery showed less pain reactions and lower heart rate mean and variation (p<0.05) than the Control Group. Conclusion: newborns who received the intervention of music combined with swaddling had less pain reactions and less variations in heart rate during venipuncture. Brazilian Clinical Trial Registry: RBR-8x8v2r.